Prevalence and Factors Associated with Excess Weight in Patients with Heart Failure in Cali, Colombia - Jhonatan Betancourt-Peña; Julieth Paola Suárez-Hernández; Guillermo Perlaza-Peláez; William Eduardo Escobar-Rodríguez; Adriana Orejuela-Upegui; Mauricio Hernández-Carrillo (Revista de Investigación e Innovación en Ciencias de la Salud)
Background. Obesity is a multifactorial disease that affects overall health and is associated with several conditions, including cardiovascular disease, diabetes, and metabolic disorders. Adipose tissue, particularly visceral adipose tissue, significantly contributes to chronic inflammation that exacerbates these comorbidities. In addition, the prevalence of heart failure and obesity in patients is high.